POSSIBILITIES OF TRAFFIC FLOW PARAMETERS TESTING AT LOSING OF THE FUNCTIONALITY OF SELECTED ROAD NETWORK ELEMENT (Perner's Contacts, 2014)
Aim of the paper is to define the options for traffic flow performance parameters testing in the in the restriction or loss of function of the road infrastructure selected element. The article contains the purpose and possibilities of traffic flow modelling, general characteristics of the software product OmniTRANS, its use in the design of the traffic organization at restrictive conditions on the segment of road and results interpretation of the solved case study.
Keywords: road infrastructure; traffic flow and its modelling; performance parameters; loss of function element